Prevalence and factors associated with substance use among street children in Jimma town, Oromiya national regional state, Ethiopia: a community based cross-sectional study - Mengistu Ayenew; Teshome Kabeta; Kifle Woldemichael (BMC, 2020)
Abstract Background Street children constitute a marginalized population in most urban centers of the world. According to UN sources, there are up to 150 million street children in the world today. The estimated number of children who live on the streets in Ethiopia was 150,000, of which about 60,000 of them in Addis Ababa. However, aid agencies estimate that the problem may be far more serious, with nearly 600,000 street children country-wide and over 100,000 in Addis Ababa. World Health Organization estimates that globally, 25-90% of street children indulge in substance use. Even if substance use has become a common problem in Ethiopia, most of the studies done mainly focused among schools, college and university students. Research on street children and their substance use habits in Ethiopia was limited and specifically non in Jimma town. Objectives To assess the prevalence and factors associated with substance use among street children in Jimma town of Ethiopia in 2019. Methods Cross sectional study was undertaken from March 1-31, 2019. Complete enumeration of study subjects was done and all 312 children of the streets were included. Interviewer administered structured questionnaires was used to collect the data. Bivariable logistic regression was carried out to select candidate for multiple logistic regression analysis with p-value < 0.25 at 95% confidence. Multiple logistic regression was carried out with those candidate variables using backward method and the associations predictors to the response variable was declared with p value of < 0.05 at 95% confidence level. Result Three hundred twelve street children were included in the study. The prevalence of substance use was 30.8% with 95% CI [25-36.2]. Age > 14 [AOR: 1.97 95%CI:1.00-3.889], attending grade 1-4th [AOR: 0.33 95%CI:0.151-0.737], attending 5th grade and above [AOR: 0.27 CI:0.093-0.756], child whose mother used substances [AOR: 7.78 95%CI:3.00-20.11], child did not know his maternal substance use status [AOR:5.1 95%CI: 2.19-11.81], child whose sibling use substance [AOR: 2.23 95%CI:1.254-5.63], best friend substance use [AOR: 11.01 95%CI:5.47-25.04] and staying 12-60 months on the street [AOR:3.00 95%CI:1.511-5.96] and staying > 5 years on the street [AOR:4.6 95%CI:1.06-19.7] were significantly associated with substance use. Conclusion and recommendation The prevalence of substance use among street children in Jimma town was high. Mothers and siblings have crucial roles in determining substance use behavior of the children. Stakeholders who are working on the improvement in the life of children of the street should try to satisfy the need of the children by intervening at individual level, at family or community level and at levels beyond community to lessen the problem to some extent. Researchers should do similar researches in more detail on these vulnerable but neglected groups of children to fully understand about the problem so the findings will be used as inputs for concerned bodies.